PENGINTEGRASIAN URGENSI DAN EKSISTENSI TANGGUNG JAWAB MUTLAK PRODUK BARANG CACAT TERSEMBUNYI PELAKU USAHA DALAM UNDANG-UNDANG PERLINDUNGAN KONSUMEN DI ERA GLOBALISASI - Holijah Holijah (Faculty of Law, Universitas Jenderal Soedirman, 2014)
The position of businessmen who have a bargaining power and bargaining position, compared to consumers’, need advocacy and protection for consumers’ right in this globalization era. This also includes an appropriate dispute resolution to achieve a Pancasila Prosperity Legal State. However, the existence of Law No. 8 Year 1999 as an umbrella act to guarantee legal assurance in fulfilling the consumer’s rights has not been effectively implemented. In the mean time, a legal protection on the prevention from hidden defect products is considerably required. This fulfilment is really needed as an alternative way to make businessmen responsible for hidden defect products. Further-more, it also needs some ideas to anticipate the urgency and the implementation in a positive norm which is not stated in Consumers’ Protection Act and is only implicitly stated on some articles on Consumers’ Protection Act. This condition hampers the realization of the consumer’s right in accordance with product liability. Key words: globalization era, consumers’ protection, product liability